Թուրքերենի Ki ստորադասական շաղկապի իմաստագործառութային դրսևորումները - Միրզոյան, Քնարիկ; Սահակյան, Լուսինե («Զանգակ - 97»)
In the modern Turkish language, the subordinate conjunctions express dependent relations, connecting the secondary clauses with the principal clause. The conjunction Ki in Turkish is an old borrowing from Iranian. As such, it has been widely used in modern Turkish, particularly in the vernacular and dialects. In the syntactic chain, it connects attributive clauses, subordinate clauses of direct object, purpose, time, cause with each other.
Keywords: Բանահյուսություն; Լեզվաբանություն